Globalization, regionalization and strategy choices for european airlines - Sarathy, Ravi (1996)
1994 was a year of recovery for the world's airlines, after combined losses for the world's top 100 airlines of $14 billion during the 1990-93 period. Even so, there was a collective net loss in 1994 of $177 million for the top 100 airlines • However, operating profit was $10.9 billion, about 4.5 % of revenues and exceeding their operating profit from the 1990-93 period. In 1994, IATA member airlines had total operating revenues of $247.5 billion, and collectively flew 2086 billion RPKs, while offering 3152 billion ASKs on their scheduled services. In this paper we study a cross section of 1994 data for 34 of the worlds largest airlines. We concentrate primarily on operating performance, financial results as well as operating statistics. Clearly, one year's results do not address the whole situation. But 1994 is a useful year to study as it marks the revival of airline industry fortunes after a long recessionary period, and studying how private and state-owned airlines were able to take advantage of industry recovery sheds light on the differences in the two groups of airlines, differences relevant to the deregulation debate